(untitled) (mathematica didactica, 2021)
Structure-genetic didactical analyses are a continuation of the traditional “subjectmatter didactics” that has been the dominating method of mathematics education in the past. However, unlike their predecessor, structure-genetic didactical analyses are not only directed to the logical structures of mathematics, but also to processes inherent in doing mathematics and to the development of genetic curricula. In this paper this research method is illustratedby typical examples (introduction of multiplication, practice of long addition, netsof cubes) and characterized as an empirical method, and it is indicated what this method isable to achieve in developmental research and in teacher education.